Reforma al código de la niñez y adolescencia, en Cuanto a la aplicación de medidas socio-educativas, Establecidas en el artículo 470 de este cuerpo legal - Arguello Najera, Agnelio Geovanny (2016)
The chosen topic for this thesis enunciates: IT "REFORMS ART. 470 OF THE CODE OF THE CHILDHOOD AND ADOLESCENCE As for THE APPLICATION OF SUBSTITUTE" MEASURES; in the same one they thought about as objective to "Carry out a juridical, critical and doctrinal study of the normative one for the application of substitute measures in the cases of adolescents in conflict with the law and their falencias in the Code of the Childhood and Adolescence." In a same way the hypothesis enunciates "The modification of substitute measures, it has impacted in the repetition of the adolescents in conflict with the law." To be able to end up checking each one of these expressions, I carried out a bibliographical investigation that served as foundation for our same field investigation that was sustained with the opinion that the substitute measures It is established therefore that the investigation framed in a doctrinal deep juridical analysis, enjoys of the validity and dependability that the professional approaches of lawyers with vast experience, for finally to present the conclusions, recommendations and the artificial reformation to the Code of the Childhood and Adolescence that I propose as solution alternative to this problem.